2008
DOI: 10.1111/j.1445-6664.2008.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple herbicide resistance in littleseed canarygrass (Phalaris minor): A threat to wheat production in India

Abstract: Littleseed canarygrass (Phalaris minor Retz.), a troublesome weed of wheat in India, has evolved multiple herbicide resistance across three modes of action: photosynthesis at the photosystem II site A, acetyl-coA carboxylase (ACCase), and acetolactate synthase inhibition.The multiple herbicide-resistant (MHR) populations had a low level of sulfosulfuron resistance but a high level of resistance to clodinafop and fenoxaprop (ACCase inhibitors). Some of the populations had GR50 (50% growth reduction) values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 66 publications
(143 reference statements)
2
73
0
Order By: Relevance
“…Similarly, of the 25 diclofop-resistant accessions of Italian ryegrass (Lolium multiflorum), five were resistant to pinoxaden (Kuk et al 2008). Chhokar and Sharma (2008) also reported the same cross-resistance pattern in little seed canary grass (P. minor). However, the cross-resistance observed in our study along with other sparse instances may imply that the selection pressure from other ACCase inhibitors can result in crossresistance to pinoxaden.…”
Section: Seed Bioassaymentioning
confidence: 58%
See 1 more Smart Citation
“…Similarly, of the 25 diclofop-resistant accessions of Italian ryegrass (Lolium multiflorum), five were resistant to pinoxaden (Kuk et al 2008). Chhokar and Sharma (2008) also reported the same cross-resistance pattern in little seed canary grass (P. minor). However, the cross-resistance observed in our study along with other sparse instances may imply that the selection pressure from other ACCase inhibitors can result in crossresistance to pinoxaden.…”
Section: Seed Bioassaymentioning
confidence: 58%
“…This has been demonstrated in a number of studies. For example, a tralkoxydim-resistant biotype of wild oat (A. fatua) (Uludag et al 2008) and clodinafop-resistant population of little seed canary grass (P. minor) (Chhokar and Sharma 2008) have shown crossresistance to pinoxaden. Cruz-Hipolito et al (2011) also found that the two A. fatua biotypes from Chile and Mexico were resistant to APP, CHD, and PPZ herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…has been distributed throughout the world and described as a troublesome weed for wheat, barley, vegetables, rotational crops and several other winter crops (Singh et al, 1999;Jabran et al, 2010). P. minor can cause up to 95% of yield reduction in wheat (Chhokar and Sharma, 2008). Manual control of P. minor is difficult because of its mimicry with wheat plants until flowering.…”
Section: Introductionmentioning
confidence: 99%
“…Many P. minor biotypes have evolved cross and multiple resistance to herbicides, having different modes of action in different parts of the world (Heap, 2015). The multiple resistance problem of P. minor at a few locations in India is so severe that it is causing huge yield reductions (Chhokar and Sharma, 2008). To prevent it from spreading to other fields and the further build-up of the herbicide resistance problem, early detection is essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation